2014
DOI: 10.1021/mp5000967
|View full text |Cite
|
Sign up to set email alerts
|

Avidity Mechanism of Dendrimer–Folic Acid Conjugates

Abstract: Multivalent conjugation of folic acid has been employed to target cells overexpressing folate receptors. Such polymer conjugates have been previously demonstrated to have high avidity to folate binding protein. However, the lack of a monovalent folic acid–polymer material has prevented a full binding analysis of these conjugates, as multivalent binding mechanisms and polymer-mass mechanisms are convoluted in samples with broad distributions of folic acid-to-dendrimer ratios. In this work, the synthesis of a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 60 publications
5
90
0
Order By: Relevance
“…Methotrexate and folic acid conjugated PAMAM dendrimer trigger the folic acid receptor corona in a two-step process with fused specific/non-specific mechanisms: first the ligand binds to the target protein leading to a conformational change; the holoprotein formed in the first step gives a favorable surface for interaction with free apoprotein leading to further aggregation onto the dendrimer-protein complex. 10, 59 Dendrimers can also be used tandemly with other nanoparticles to optimize their biological response.…”
Section: R a F Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Methotrexate and folic acid conjugated PAMAM dendrimer trigger the folic acid receptor corona in a two-step process with fused specific/non-specific mechanisms: first the ligand binds to the target protein leading to a conformational change; the holoprotein formed in the first step gives a favorable surface for interaction with free apoprotein leading to further aggregation onto the dendrimer-protein complex. 10, 59 Dendrimers can also be used tandemly with other nanoparticles to optimize their biological response.…”
Section: R a F Tmentioning
confidence: 99%
“…Methotrexate and folic acid conjugated PAMAM dendrimer trigger the folic acid receptor corona in a two-step process with fused specific/non-specific mechanisms: first the ligand binds to the target protein leading to a conformational change; the holoprotein formed in the first step gives a favorable surface for interaction with free apoprotein leading to further aggregation onto the dendrimer-protein complex. 10,59 Dendrimers can also be used tandemly with other nanoparticles to optimize their biological response.Antibody conjugated dendrimer-encapsulated gold nanoparticles can afford enhanced sensitivity for protein detection due to protein amplifications on dendrimer surface. 60 The increased sensitivity utilized the high density of reactive arms on the dendrimer surface, leading to higher local concentration of antibody and subsequently target proteins.…”
mentioning
confidence: 99%
“…Binding of the substrates D-glucose and sodium reduced hydrophobicity, whereas binding of phlorizin, an inhibitor of glucose transport, induced a more hydrophobic conformation less suitable for trans-membrane transport [47]. A recent study points to another effect of the ligand-induced changes in surface hydrophobicity of FBP [48]. Binding between a certain type of chemotherapeutic agents, dendrimer conjugates of folic acid, and immobilized FBP is a two-step mechanism.…”
Section: Surface Hydrophobicitymentioning
confidence: 99%
“…Binding between a certain type of chemotherapeutic agents, dendrimer conjugates of folic acid, and immobilized FBP is a two-step mechanism. The first step is keyed by binding of conjugated folic acid, which in the second step brings the dendrimer arms of the conjugate into close contact with the protein [48]. The authors assume that the initial binding of conjugated folate to FBP results in a conformational change with exposure of a hydrophilic surface that enables an irreversible van der Waals interaction with the dendrimer.…”
Section: Surface Hydrophobicitymentioning
confidence: 99%
“…We demonstrated that rp-HPLC can be used to separate trailing and branching defects in poly(amidoamine) (PAMAM) dendrimers 25 and separate species with different numbers of hydrophobic ligands (dyes, drugs, targeting agents) attached to the hydrophilic backbone. 610 AFM allowed for direct, representative imaging of samples and surfaces with nanometer precision in the x and y directions and subnanometer precision vertically. 1121 Importantly, AFM is a topographic technique, measuring the volume of imaged features along with surface morphology and material properties.…”
Section: Introductionmentioning
confidence: 99%